Border Watch Cultures of Immigration, Detention and Control - Hall, Alexandra (Pluto Press, 2012)
Questions over immigration and asylum face almost all Western countries. Should only economically useful immigrants be allowed? What should be done with unwanted or 'illegal' immigrants? In this bold intervention, Alexandra Hall shows that immigration detention centres offer a window onto society's broader attitudes towards immigrants. Despite periodic media scandals, remarkably little has been written about the everyday workings of this system, or about the people responsible for setting immigration policy. Detention, particularly, is a hidden side of border politics, despite its growing international importance as a tool of control and security. This book also looks at the social life and the relationships between officers and immigrants to explore broad social trends, as well as resistance within the system, and provides rare insights into the treatment of the 'other'.